Fabrication of CdSe nanoparticles sensitized TiO2 nanotube arrays via pulse electrodeposition for photoelectrochemical application. (October 2018) - Ayal, Asmaa Kadim; Zainal, Zulkarnain; Lim, Hong Ngee; Talib, Zainal Abidin; Lim, Ying-Chin; Chang, Sook-Keng; Holi, Araa Mebdir
Graphical abstract: Highlights: Anodization method approach for the synthesis of TiO2 nanotubes. CdSe nanoparticle/TiO2 nanotube arrays were assembled via pulse electrochemical deposition technique. Duty cycles were applied in order to enhance the properties of CdSe/TiO2 nanostructure. PEC analysis verified that CdSe/TiO2 structure prepared at 50% duty cycle gave best photocurrent response. Photoconversion efficiency of CdSe/TiO2 nanostructure was approximately 59 times greater than TiO2 nanotubes. Abstract: Solar energy is an alternative sustainable energy resource that can be harvested using photoelectrochemical cell comprised of inorganic sensitized nanostructured oxide semiconductor electrode. In this work, pulse electrodeposition was used to deposit CdSe onto titanium dioxide nanotube arrays (TiO2 NTAs). TiO2 NTAs are commonly used in the nanostructured photoelectrochemical cells due to their high surface area, fewer interfacial grain boundaries and excellent charge transfer between interfaces. Duty cycle of pulse electrodeposition played an important role in the formation of CdSe nanoparticles. A significant enhancement in the photoelectrochemical performance was observed for the heterostructure of CdSe/TiO2 NTAs. CdSe/TiO2 NTAs prepared at 50% duty cycle exhibited maximum photocurrent of 1.94 mA cm −2 and photoconversion efficiency of 1.18% which was 59 times higher than bare TiO2 NTAs. These results demonstrated that significant enhancement in the photoconversion efficiency could be obtained by incorporating CdSe as sensitizer into the TiO2 nanotube arrays via pulse electrodeposition technique.